A Neglected Issue in North Cyprus: Sexual Education - Önay Aktunç; Nilsu Atıcı; Dilek Sarpkaya Güder (Galenos Publishing House, 2024)
In the light of current studies on sexual education in North Cyprus, this study has been prepared in order to contribute to the relevant literature and to raise awareness about the importance of sexual education which is a neglected subject. The study is a review type. The research methods used in the study are descriptive and documentary analysis methods. Current studies made in the last five years (2018-2023) in North Cyprus were included in the scope of the study. Sex education is explained as a lifelong process that includes biological, socio-cultural, psychological and spiritual dimensions, including cognitive learning, affective learning and behavioral learning. All people have the right to take comprehensive sexuality education. Comprehensive school-based sexuality education should be part of the education program at all levels. Main topics for all age groups are the human body and development, fertility and reproduction, sexuality, emotions, lifestyle and relationships, sexual health and well-being, sexuality and rights, and social and cultural determinants of sexuality. Sex education is not included in the primary and secondary education curriculum in North Cyprus. It is stated that there is the subject of "protection from danger and abuse" in the life studies curriculum in primary and secondary education. Three studies related to child abuse were found when the studies within the scope of the study are examined in North Cyprus. One study is related to sexual orientation and one study is related to gender roles. As a result of a study conducted with parents with children aged 8-10 in the country, it was determined that only 50% of parents could identify with the type of child abuse, and suggestions were given for their children to be educated on this issue. In another study conducted with parents of 4-6 year-old children, it was determined that parents had moderate awareness of sexual abuse and did not have sufficient knowledge. In another study, it was found that parents with pre-school children aged 3-6 did not find themselves sufficient in providing sexual education and there was a significant relationship between their knowledge levels about sexual education and their children's attitudes. In a study conducted with young adults, the attitude scores of young people towards gender roles were determined to be prone to egalitarian attitudes. When the existing studies in North Cyprus are examined, it is seen that there are not many studies on sexual education in the country and sexual education is not given in primary and secondary education levels. Therefore, the greatest responsibility for sexual education lies to the parents. It is recommended to include school-based sexual education in basic education programs, to conduct studies on all subjects within the scope of sexual education, and to organize awareness trainings on the subject for teachers and parents. In addition, school nurses should be supported to initiate school-based sexual education and to take an active role in education.